A peptide that blocks the interaction of NF‐κB p65 subunit with Smad4 enhances BMP2‐induced osteogenesis. Issue 9 (16th April 2018) - Urata, Mariko; Kokabu, Shoichiro; Matsubara, Takuma; Sugiyama, Goro; Nakatomi, Chihiro; Takeuchi, Hiroshi; Hirata‐Tsuchiya, Shizu; Aoki, Kazuhiro; Tamura, Yukihiko; Moriyama, Yasuko; Ayukawa, Yasunori; Matsuda, Miho; et al.
Abstract : Bone morphogenetic protein (BMP) potentiates bone formation through the Smad signaling pathway in vitro and in vivo. The transcription factor nuclear factor κB (NF‐κB) suppresses BMP‐induced osteoblast differentiation. Recently, we identified that the transactivation (TA) 2 domain of p65, a main subunit of NF‐κB, interacts with the mad homology (MH) 1 domain of Smad4 to inhibit BMP signaling. Therefore, we further attempted to identify the interacting regions of these two molecules at the amino acid level. We identified a region that we term the Smad4‐binding domain (SBD), an amino‐terminal region of TA2 that associates with the MH1 domain of Smad4. Cell‐permeable SBD peptide blocked the association of p65 with Smad4 and enhanced BMP2‐induced osteoblast differentiation and mineralization without affecting the phosphorylation of Smad1/5 or the activation of NF‐κB signaling. SBD peptide enhanced the binding of the BMP2‐inudced phosphorylated Smad1/5 on the promoter region of inhibitor of DNA binding 1 (Id‐1) compared with control peptide. Although SBD peptide did not affect BMP2‐induced chondrogenesis during ectopic bone formation, the peptide enhanced BMP2‐induced ectopic bone formation in subcortical bone. Thus, the SBD peptide is useful for enabling BMP2‐induced bone regeneration without inhibiting NF‐κB activity. Abstract : We attempted to identify the interacting regions of p65 TA2 domain and Smad4 MH1 domain at the amino acid level. We identified a region that we term the Smad4‐binding domain (SBD), an amino‐terminal region of TA2 that associates with the MH1 domain of Smad4. Cell‐permeable SBD peptide blocked the association of p65 with Smad4 and enhanced BMP2‐induced osteoblast differentiation and mineralization without affecting the phosphorylation of Smad1/5 or the activation of NF‐κB signaling. The peptide enhanced BMP2‐induced ectopic bone formation in subcortical bone.